Hadith on the Prohibition of Women Traveling without a Mahram (Application of Hermeneutic Theory Jorge J. E. Gracia) - Ulummudin, Ulummudin (Journal of Hadith Studies, 2018)
This paper examines the hadith prohibiting women from traveling without a ma?ram through the lens of Jorge J. E. Gracia’s hermeneutic theory. A textual analysis utilizing three interpretive functions yields the following results: the historical function of the hadith is linked to the contexts of Hajj and war; the function of meaning suggests that women could travel without a ma?ram, provided there is a shift in context; and the function of implication indicates that women could assume a more active societal role beyond the domestic sphere. Additionally, non-textual readings highlight that the core idea of this hadith is protection, aimed at ensuring safety and security. In this context, the concept of ma?ram evolves to represent a security figure capable of providing assistance.